CHARACTERISTICS MILK PRODUCTION OF COWS WITH DIFFERENT BODY COMPOSITION (World Bulletin of Management and Law, 2022)
In the researches, Simmental breed cows with milk and milk-meat body composition III and above lactation were characterized by high milk productivity during lactation, and it was also found that they have the properties of covering feed with milk products at a high level. These results have been found to be of great practical importance in creating dairy herds from high-yielding cows and determining their efficiency in carrying out selection work taking into account body structure types, determining efficiency in cattle breeding